Impact of Nested Moisture Cycles on Coastal Chalk Cliff Failure Revealed by Multiseasonal Seismic and Topographic Surveys. Issue 8 (26th August 2020) - Dietze, M.; Cook, K. L.; Illien, L.; Rach, O.; Puffpaff, S.; Stodian, I.; Hovius, N.
Abstract : Cliff failure is a fundamental process shaping many coastlines worldwide. Improved insight into direct links between cliff failure and forcing mechanisms requires precise information on the timing of individual failures, which is difficult to obtain with conventional observation methods for longer stretches of coastline. Here we use seismic records and auxiliary data spanning 25 months to precisely identify and locate 81 failure events along the 8.6‐km‐long chalk cliff coast of Jasmund, on Germany's largest island, Rügen. The subminute precision of event timing allows the linkage of individual failures to triggers over a wide range of relevant time scales. We show that during the monitoring interval, marine processes were negligible as a trigger of cliff failure, although still being important for the removal of resulting deposits. Instead, cliff failure was associated with terrestrial controls on rock moisture. Most failures occurred when water caused a state transition of the cliff forming chalk, from solid to liquid. Water content was modulated by (i) subsurface flow toward the cliff, (ii) rain onto the cliff, and (iii) condensation of atmospheric moisture, leading to clustered failures preferentially during the night. Seasonal water availability, controlled by plant activity, imposed an annual cycle of cliff failure, and wetter and drier than average years imposed a month‐long legacy effect on cliff failure dynamics. Similar terrestrial control mechanisms may also be relevant for other coastal chalk cliffs, in addition to already investigated marine triggers. Plain Language Summary: Cliffs line many coastlines worldwide. They are eroded by cliff falls, with consequences for human safety, land loss, ecosystem dynamics, and availability of sediment along the coast. The discrepancy between rapid, short‐lived failure processes and episodic observation techniques does not allow for a full analysis of the causes and drivers of cliff erosion. Combining measurements from a seismometer network on Germany's largest island, Rügen, with 3‐D models from drone surveys and weather station data, we detected, located, and timed 81 cliff failures in 2 years and analyzed the circumstances that gave rise to their occurrence. These events were predominantly associated with the presence of water, which turns the solid, cliff‐building chalk into a failure‐prone slurry. Water availability is modulated at different time scales by rain on the cliff and moisture condensation, soil water flow, vegetation water uptake, and possibly the lunar cycle. Our findings sharpen the picture of when and why cliffs fail and offer a better prediction of the impact of global change on cliff coasts. Key Points: Multiyear UAV and seismic monitoring yielded a catalogue comprising timing, propagation, and location of 81 coastal cliff failures Failures are controlled by water availability through subsurface flow, rain, and atmospheric moisture condensation Failures are controlled on diurnal, monthly, seasonal, and multiyear scales